Atomic-resolution imaging of the polar (0001¯) surface of LiNbO3in aqueous solution by frequency modulation atomic force microscopy - Rode, S.; Hölscher, R.; Sanna, S.; Klassen, S.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Fingerprints of order and disorder in the electronic and optical properties of crystalline and amorphous TiO2 - Landmann, M.; Köhler, T.; Köppen, S.; Rauls, E.; Frauenheim, T.; Schmidt, Wolf Gero (Physical Review B)

Activation of Surface Hydroxyl Groups by Modification of H-Terminated Si(111) Surfaces - Thissen, Peter; Peixoto, Tatiana; Longo, Roberto C.; Peng, Weina; Schmidt, Wolf Gero; Cho, Kyeongjae; Chabal, Yves J. (Journal of the American Chemical Society)

Interplay between metal-free phthalocyanine molecules and Au(110) substrates - Rauls, E.; Schmidt, Wolf Gero; Pertram, T.; Wandelt, K. (Surface Science)

The electronic structure and optical response of rutile, anatase and brookite TiO2 - Landmann, M; Rauls, E; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

2-Aminopyrimidine-silver(I) based organic semiconductors: Electronic structure and optical response - Riefer, A.; Rauls, E.; Schmidt, Wolf Gero; Eberhard, J.; Stoll, I.; Mattay, J. (Physical Review B)

pH-dependent structure and energetics of H2O/MgO(100) - Thissen, Peter; Thissen, Vera; Wippermann, Stefan; Chabal, Yves J.; Grundmeier, Guido; Schmidt, Wolf Gero (Surface Science)

Adsorption of OH and H at the LiNbO3(0001) surface - Hölscher, R.; Sanna, S.; Schmidt, Wolf Gero (physica status solidi (c))

In-Si(111)(4 × 1)/(8 × 2) nanowires: Electron transport, entropy, and metal-insulator transition - Schmidt, Wolf Gero; Wippermann, S.; Sanna, S.; Babilon, M.; Vollmers, N. J.; Gerstmann, Uwe (physica status solidi (b))

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, Cedrik (Optics Express)

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, C. (Optics Express)

Cavity-assisted emission of polarization-entangled photons from biexcitons in quantum dots with fine-structure splitting - Schumacher, Stefan; Förstner, Jens; Zrenner, Artur; Florian, Matthias; Gies, Christopher; Gartner, Paul; Jahnke, Frank (Optics Express)
We study the quantum properties and statistics of photons emitted by a quantum-dot biexciton inside a cavity. In the biexciton-exciton cascade, fine-structure splitting between exciton levels degrades polarization-entanglement for the emitted pair of photons. However, here we show that the polarization-entanglement can be preserved in such a system through simultaneous emission of two degenerate photons into cavity modes tuned to half the biexciton energy. Based on detailed theoretical calculations for realistic quantum-dot and cavity parameters, we quantify the degree of achievable entanglement.
Keywords: tet_topic_qd

Optimization of the intensity enhancement in plasmonic nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens
We design the geometrical shape of plasmonic nanostructures to achieve field patterns with desired properties. For this, we combine Maxwell simulations and automatic optimization techniques. By allowing variations of the geometrical shape, which can be based on either boxes or arbitrary polygons, we maximize the desired objective.
Keywords: tet_topic_optical antenna; tet_topic_plasmonics

A 2D Quantum Walk Simulation of Two-Particle Dynamics - Schreiber, Andreas; Gábris, Aurél; Rohde, Peter P.; Laiho, Kaisa; Štefaňák, Martin; Potoček, Václav; Hamilton, Craig; Jex, Igor; Silberhorn, Christine (Science)
Here, There, Everywhere Random walks are a powerful mathematical method that can be used to simulate certain processes in biology, chemistry, or even the stock market. They present a statistical method for mapping the possible routes that processes can take. Quantum walks are expected to be able to probe multiple paths simultaneously. Quantum walks have been demonstrated for one-dimensional, or straight-line, walks. Now, Schreiber et al. (p. 55 , published online 8 March) demonstrate an optical system that can simulate quantum walks over a two-dimensional system, thereby providing the capability of describing much more complex processes.
Keywords: Multidisciplinary

Limits on the deterministic creation of pure single-photon states using parametric down-conversion - Christ, Andreas; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Dynamics of ionisation and entanglement in the 'atom + quantum electromagnetic field' system - Sharapova, Polina; Tikhonova, O V (Quantum Electronics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Statistical and Nonlinear Physics; Electronic; Optical and Magnetic Materials

„Praktische Aktivitäten“ im physikbezogenen Sachunterricht der Grundschule und im physikalischen Anfangsunterricht der Sekundarstufe – ein Vergleich. - Tenberge, Claudia; Lange, Kim; Möller, Kornalia (Bedingungen des Lehrens und Lernens in der Grundschule – Bilanz und Perspektiven.)

High resolution time-to-space conversion of sub-picosecond pulses at 155µm by non-degenerate SFG in PPLN crystal - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Exponentially enhanced quantum communication rate by multiplexing continuous-variable teleportation - Christ, Andreas; Lupo, Cosmo; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy